1993
DOI: 10.1007/bf02236235
|View full text |Cite
|
Sign up to set email alerts
|

A survey of mineral status of soils, feeds and cattle in the Selale Ethiopian highlands. I. Macro elements

Abstract: The macro mineral status of cattle in the Selale highlands of Ethiopia was evaluated during the rainy and dry seasons of 1989 and 1990 in terms of mineral concentrations in soils, feeds, blood plasma and faeces on 25 farms. Bone samples from animals of local breeds from a slaughter house were collected during the rainy and dry seasons of 1990. Soils were analysed for pH, organic matter, Ca, P, Mg, Na and K. The results indicated wide variation in the concentrations of minerals on different farms. Available fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
1
6
2
Order By: Relevance
“…Similar fluctuations in forage Fe levels have already been reported by Kuhn et al [26] and Angelow et al [27] while studying the mineral contents of various forage crops. Forage Fe values found in the present study were lower than those reported by Prabowo et al [23] in Indonesia, Espinoza et al [20] in central Florida, Khan et al [8,19] and Ahmad et al [28] in Pakistan, and Khalili et al [21] in Finland.…”
Section: Transfer Of Fe In the Soil-plant Systemcontrasting
confidence: 80%
See 2 more Smart Citations
“…Similar fluctuations in forage Fe levels have already been reported by Kuhn et al [26] and Angelow et al [27] while studying the mineral contents of various forage crops. Forage Fe values found in the present study were lower than those reported by Prabowo et al [23] in Indonesia, Espinoza et al [20] in central Florida, Khan et al [8,19] and Ahmad et al [28] in Pakistan, and Khalili et al [21] in Finland.…”
Section: Transfer Of Fe In the Soil-plant Systemcontrasting
confidence: 80%
“…These soil Fe values were lower than those reported by Tejada et al [17,18] in Guatemala, Khan et al [19] in Pakistan, and Espinoza et al [20] in central Florida. However, these values were lower than those reported by Khalili et al [21] in Finland, Pastrana et al [22] in Columbia, and Prabowo et al [23] in Indonesia.…”
Section: Transfer Of Fe In the Soil-plant Systemcontrasting
confidence: 77%
See 1 more Smart Citation
“…This is consistent with the report of Playne (1970) who observed differences in Na content between the Poineer and Callide cultivars of tropical forage, Chloris gayana. The Na content of the leaf lamina, leaf midrib, pseudostem and corm of different varieties was mostly lower than the value reported for pasture, hay and straws (Khalili et al 1993a;Kabaija and Little 1988). The Na contents in all varieties and fractions were below the recommended level for ruminants (Table 6).…”
Section: Sodiummentioning
confidence: 63%
“…For example, higher incidences of liver Cu deficiencies (<75 mg/kg DM) are reported in the wet than in the dry season in beef cattle from Malawi (Mtimuni et al, 1990), St. Croix (Wildeus et al, 1992) and Ethiopia (Khalili et al, 1993). Additionally Zn, Fe and Mn levels are lower in the wet than in the dry season in beef cattle from Malawi (Mtimuni et al, 1990).…”
Section: Introductionmentioning
confidence: 99%